2017
DOI: 10.1186/s12978-017-0417-z
|View full text |Cite
|
Sign up to set email alerts
|

State of newborn care in South Sudan’s displacement camps: a descriptive study of facility-based deliveries

Abstract: BackgroundApproximately 2.7 million neonatal deaths occur annually, with highest rates of neonatal mortality in countries that have recently experienced conflict. Constant instability in South Sudan further strains a weakened health system and poses public health challenges during the neonatal period. We aimed to describe the state of newborn facility-level care in displaced person camps across Juba, Malakal, and Maban.MethodsWe conducted clinical observations of the labor and delivery period, exit interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 29 publications
2
60
2
Order By: Relevance
“…38 Sexually transmitted diseases (STIs) and HIV/AIDS were not a major focus in the SRH interventions. 35,38,51,57,63 Most interventions lasted for longer durations (up to three years) 35,51 compared to other intervention types. Reasons given for shorter SRH intervention periods included poor sustainability and high-cost implications.…”
Section: Sexual Reproductive Maternal and Child Health Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…38 Sexually transmitted diseases (STIs) and HIV/AIDS were not a major focus in the SRH interventions. 35,38,51,57,63 Most interventions lasted for longer durations (up to three years) 35,51 compared to other intervention types. Reasons given for shorter SRH intervention periods included poor sustainability and high-cost implications.…”
Section: Sexual Reproductive Maternal and Child Health Interventionsmentioning
confidence: 99%
“…health workers and essential supplies, especially the provision of FP commodities for pregnancy risk reduction. 51,57 A study on newborn care reported lack of newborn services and wide disparities in the care provided at primary care levels compared to secondary care (hospitals). Difference in the quality of health services between the two levels of care was evident in the higher number of recommended essential drugs available at the hospitals (20/37) compared to primary care facilities (9/25).…”
Section: Sexual Reproductive Maternal and Child Health Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postnatal home visits in the first week of life, while new and acceptable to community health workers (CHWs), were not sustained during periods of mass displacement because of the inability to locate households and limited staff available to manage competing priorities (11). At the facility level, partograph use for fetal monitoring, skin-to-skin contact, and postnatal monitoring of danger signs were the least commonly used practices at baseline, highlighting gaps in care for small and sick newborns (9). Despite this, essential newborn practices such as thermal care (immediate drying and wrapping), infection prevention, and feeding support were high following the intervention (ranging from 79.7% to 83.2%).…”
mentioning
confidence: 99%